Are there narcissistic career choices? An investigation of narcissistic traits and vocational interests. (April 2023) - Velji, Jenna; Kowalski, Christopher Marcin; Schermer, Julie Aitken
Abstract: The present study focused on the relationships between vocational interests and 11 scales associated with narcissistic grandiosity and four scales associated with narcissistic vulnerability based on results from a convenience sample of 716 undergraduate business management students. Past research suggests vulnerable and grandiose narcissism differ significantly in their empirical correlates; thus, we expected scales capturing narcissistic grandiosity and narcissistic vulnerability to display diverging patterns of correlation with the vocational interest scales. Our results generally supported this prediction. Vulnerable narcissism scores generally had positive correlations with artistic, social, and applied interests. In contrast, grandiose narcissism scores had significant correlations with science and business interests and negative correlations with workstyle dimensions, such as accountability. Limitations and future research suggestions are discussed.